USING CHUNKING TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION OF SMPN 36 MAKASSAR - Firman, Firman (Fakultas Keguruan dan Ilmu Pendidikan, 2016)
This research aims at finding out the achievement and interest of Chunking technique in improving reading comprehension at the ninth grade of SMP Negeri 36 Makassar. The specific objectives of the research were to find out whether or not the using of Chunking technique can improve students comprehension in reading and to find out the students’ interest in learning reading comprehension by use of Chunking technique. The research method employed quasi-experimental research. The samples consist of 58 students which belonged to two groups; 28 students in experimental group and 28 students in control group. The data of the research were found using two kinds of instruments; the test of reading for the students’ comprehension in reading and questionnaire of students’ interest which were analyzed by SPSS version 17.0 The research result indicated that: (1) using of Chunking technique has a significant effect to improve the reading comprehension of the ninth grade of SMP Negeri 36 Makassar. The students’ result of posttest for experimental group was higher than the students’ result posttest for control group. It was proven by showing the result of the mean score of posttest of experimental was higher than the control group in reading comprehension (78.04 > 66.54). It means that by applying of Chunking technique improved the students reading comprehension. This research also found that (2) the students’ interest toward Chunking technique is high. Most of the students were interested in learning reading comprehension toward Chunking technique.